Cybersecurity of Smart Grids: Attacks and Defenses of the Smart Meters in an Advanced Metering Infrastructure (AMI) - Jacoba, Gian Lloyd B.; Genove, Gerry Paul C. (Southeast Asian Journal of Science and Technology, 2023)
Together with the rising energy demand, newer challenges come with it. The paper analyzes the cybersecurity challenges and defenses accompanying the smart grid, particularly Smart Meters in an Advanced Metering Infrastructure (AMI). The Advanced Metering Infrastructure provides intelligent systems connecting the customers and the energy service providers. These AMIs are essential in keeping track of the customer’s data because of their real-time capability and smart options that were integrated. It is then necessary to protect the AMI because it can cripple entire smart grids and leave the population vulnerable to elements. Based on the literature review, the most common attacks in the AMI are Eavesdropping, Denial of Service, False Data Injection, Remote Connect/Disconnect Firmware Manipulation, Man-in-the-Middle, and Power Hijacking. The most potent defenses the literature review has found to employ are Data Encryption, Authentication, and Intrusion Detection Systems.